Development of a Student Bullying Scale Using the Rasch Model - Suryana, Agus; Akbar, Maruf; Ridwan, Achmad (KnE Social Sciences, 2020)
Student bullying scales have been developed based on Western cultures, however these are not necessarily applicable to non-Western cultures, and there is a need for a scale to measure bullying behaviours that is adaptable to individual national cultures. This would not only be useful for students undergoing bullying, but also useful from the perpetrator’s side. The Rasch model can be used in this fashion, and this study seeks to develop a student bullying scale by applying the psychometric properties of the Rasch model. The dimensions of the bullying scale consisted of power imbalance, intent to harm, and cyberbullying, and the bullying indicators are defined as verbal, physical, visual, and relational. A total of 1200 public junior high school students in Bogor Regency took part in the study divided of 500 students in phase 1 and 700 students in phase II. The study concludes that the proposed instrument to evaluate bullying has significant validity and reliability in both phase 1 and phase 2. Keywords: rasch model, bullying scale, validity and reliabilty